Analysis of Risk Factors for the Incidence of Hyperemesis Gravidarum at RSIA Fatimah and at RSUD Haji Makassar - Husnul Khatimah; Rini Fitriani; Fhirastika Annisha Helvian; Rista Suryaningsih; Darsul S. Puyu (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: 32.26% of pregnant women in South Sulawesi in 2018 experienced disorders or complications during their pregnancy, 24.3% of them experienced disorders in the form of continuous vomiting / diarrhea. If nausea and vomiting occurs more than 5 times a day, it is called hyperemesis gravidarum. One of the risk factors for hyperemesis gravidarum is education. a person's education greatly affects the ability to think and the level of understanding and acceptance of something that is conveyed. Objective: This study aims to analyze the risk factors for the occurrence of hyperemesis gravidarum in pregnant women at the Fatimah Mother and Child Hospital and at the Regional General Hospital Haji Makassar. Method: This type of research is an observational analytic research with a case control approach. The population and sample used are all pregnant women who are recorded in the register book for 2020-2022 at RSIA Fatimah Makassar and RSUD Haji Makassar with a sample of 75 cases and controls that met the inclusion criteria. Result: The results showed that the prevalence of hyperemesis gravidarum at RSIA Fatimah Makassar and RSU Haji Makassar 2020-2022 was 50% (n = 75). The results of statistical analysis were mother's age OR 0.389 (95% CI = 0.174-0.870), Parity OR 0.469 (95% CI = 0.244-0.901), Education OR 3.083 (95% CI = 1.536-6.190), Occupation OR 1.158 ( CI 95% = 0.547-2.451), The results of bivariate analysis, namely maternal education OR 3.083 (95% CI = 1.536-6.190) is a risk factor for the occurrence of hyperemesis gravidarum. Conclusion: Maternal education is a risk factor for hyperemesis gravidarum with an OR value of 3.083 > 1 and a p-value = 0.002 <0.05.